Answer:
x=3 and y=−2
Explanation:
Multiply the first equation by 4,and multiply the second equation by 3.
4(2x−3y=12)
3(3x+4y=1)
Becomes:
8x−12y=48
9x+12y=3
Add these equations to eliminate y:
17x=51
Then solve17x=51for x:
17x=51
17x
17
=
51
17
(Divide both sides by 17)
x=3
Now that we've found x let's plug it back in to solve for y.
Write down an original equation:
2x−3y=12
Substitute3forxin2x−3y=12:
(2)(3)−3y=12
−3y+6=12(Simplify both sides of the equation)
−3y+6+−6=12+−6(Add -6 to both sides)
−3y=6
−3y
−3
=
6
−3
(Divide both sides by -3)
y=−2